Pengaruh Persepsi Dan Pemahaman Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Pada PP No 23 Terhadap Umkm Di Kota Medan Sumatera Utara - Yeni Yolanda Simatupang; Lira Amelia; Fitrah Khairuna Ulfa Lubis (Pajak dan Manajemen Keuangan, 2024)
This research investigates the understanding and compliance of MSMEs in Medan City regarding Government Regulation No. 23 of 2018, which provides tax facilities. Findings from surveys and in-depth interviews with 100 MSMEs reveal that the majority (78%) have a good understanding of the regulation. They also perceive this regulation as beneficial in managing their business tax aspects (82%). Tax compliance has also improved, with 70% of respondents reporting adherence to tax regulations since understanding the regulation. Factors influencing understanding and compliance include effective socialization, technological support, and respondents' educational levels. The implications of this study underscore the importance of continuous government efforts in socialization and education, as well as ensuring accessible services for MSMEs, to enhance tax compliance and support sustainable regional economic growth.